Multimodal imaging in a pedigree of X-linked Retinoschisis with a novel RS1 variant - Stephenson, Kirk; Dockery, Adrian; Wynne, Niamh; Carrigan, Matthew; Kenna, Paul; Jane Farrar, G.; Keegan, David (BMC medical genetics, 2018)
Background To describe the clinical phenotype and genetic cause underlying the disease pathology in a pedigree (affected n = 9) with X-linked retinoschisis (XLRS1) due to a novel RS1 mutation and to assess suitability for novel therapies using multimodal imaging. Methods The Irish National Registry for Inherited Retinal Degenerations (Target 5000) is a program including clinical history and examination with multimodal retinal imaging, electrophysiology, visual field testing and genetic analysis. Nine affected patients were identified across 3 generations of an XLRS1 pedigree. DNA sequencing was performed for each patient, one carrier female and one unaffected relative. Pedigree mapping revealed a further 4 affected males. Results All affected patients had a history of reduced visual acuity and dyschromatopsia; however, the severity of phenotype varied widely between the nine affected subjects. The stage of disease was classified as previously described. Phenotypic severity was not linearly correlated with age. A novel RS1 (Xp22.2) mutation was detected (NM_000330: c.413C > A) resulting in a p.Thr138Asn substitution. Protein modelling demonstrated a change in higher order protein folding that is likely pathogenic. Conclusions This family has a novel gene mutation in RS1 with clinical evidence of XLRS1. A proportion of the older generation has developed end-stage macular atrophy; however, the severity is variable. Confirmation of genotype in the affected grandsons of this pedigree in principle may enable them to avail of upcoming gene therapies, provided there is anatomical evidence (from multimodal imaging) of potentially reversible early stage disease.